2018
DOI: 10.1159/000494543
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Management of Antiplatelet-Related Bleeding Complications for Acute Coronary Syndrome in Chinese Elderly Patients

Abstract: Background/Aims: Bleeding complications after percutaneous coronary intervention (PCI) are strongly associated with adverse patient outcomes. However, there are no specific guidelines for the predictors and management of antiplatelet-related bleeding complications in Chinese elderly patients with acute coronary syndrome (ACS). Methods: A retrospective analysis of 237 consecutive patients (aged ≥ 75 years) with ACS who had undergone successful PCI from January 2010 to December 2016 was performed to identify pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…[ 11 ] A retrospective Chinese study over 6 years on elderly patients above 75 years age who underwent PCI reported a GI bleed rate of 16.5% with no rebleed after reintroduction of drugs. [ 6 ] Western studies appear to have lower incidence of GI bleed in the long term (i.e. it falls off in later years) but our results are more in conformity with the Chinese study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[ 11 ] A retrospective Chinese study over 6 years on elderly patients above 75 years age who underwent PCI reported a GI bleed rate of 16.5% with no rebleed after reintroduction of drugs. [ 6 ] Western studies appear to have lower incidence of GI bleed in the long term (i.e. it falls off in later years) but our results are more in conformity with the Chinese study.…”
Section: Discussionsupporting
confidence: 84%
“…[ 5 ] Data are sparser from the eastern world. [ 6 ] The present study was aimed to delineate the long term incidence of GI bleed, rebleed, treatment outcome and mortality as also any difference therein among the patient groups receiving the above medications for various indications. With rising elderly population in resource limited Indian settings, many primary care providers will have to deal with problems in this patient group early in their course.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in this study, female patients of AMI were much older, had lower levels of education with more of them living without their spouses, and therefore were more likely to neglect the necessity of longterm medication including antiplatelet therapy and statins. Besides, female patients of AMI were more likely to have complications caused by antiplatelet therapy and statins [30][31][32]. Tis might also be one of the reasons why more female patients of AMI were poorly adherent to antiplatelet therapy and statins.…”
Section: Discussionmentioning
confidence: 99%